Web Information Systems and Technologies 9th International Conference, WEBIST 2013, Aachen, Germany, May 8-10, 2013, Revised Selected Papers - Krempels, Karl-Heinz.; Stocker, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book contains the thoroughly refereed and revised best papers from the 9th International Conference on Web Information Systems and Technologies, WEBIST 2013, held in Aachen, Germany, in May 2013, organized by the Institute for Systems and Technologies of Information, Control and Communication (INSTICC), and co-organized by the RWTH Aachen University. The 15 papers presented in this book were carefully reviewed and selected from 143 submissions. The papers were selected from those with the best reviews also taking into account the quality of their presentation at the conference. The papers are grouped into parts on Internet technology, Web interfaces and applications, society, e-business and e-government, Web intelligence, and mobile information systems.
Part: Internet Technology -- Networked XML Compression by Encoding Pre-order Traversals -- Generating XACML Enforcement Policies for Role-Based Access Control of XML Documents -- Engineering Flexible Service-Oriented Transactions -- HTML5 Agents: Mobile Agents for the Web -- Watermarking Digital Images in the Frequency Domain: Performance and Attack Issues -- Part: Web Interfaces and Applications -- Towards a Web of Semantic Tags -- Web Service Discovery and Execution Using a Dialog-Based Approach -- Comparison of Mobile Web Frameworks -- Improving Search Engines$1 (BDocument Ranking Employing Semantics and an Inference Network -- Category-Based YouTube Request Pattern Characterization -- Society, e-Business and e-Government -- Enhancing the Modularity and Applicability of Web-Based Signature-Verification Tools -- Status Quo and Best Practices of App Development in Regional Companies -- Web Intelligence -- Vector Space Models for the Classification of Short Messages on Social Network Services -- FactRunner: A New System for NLP-Based Information Extraction from Wikipedia -- Mobile Information Systems -- Context and Activity Recognition for Personalized Mobile Recommendations.s
Keywords: Computer science; Information technology; Business -- Data processing; Software engineering; E-commerce.; Computer Science; Information Systems Applications (incl. Internet).; IT in Business; e-Commerce/e-business.; Software Engineering; Electronic books